DeSci EDU: course design and self-perceived evaluation in decentralized science education - Espinoza, S.; Kumar, K.; Laredo, F.; Compton, K.; Yanik, C.; Bishop-Currey, L.; McCarthy-Page, E.; Lukács, B.; Weidener, L. (Frontiers in Blockchain, 2026)
IntroductionDecentralized science (DeSci) aims to address structural inefficiencies in traditional research yet lacks formal educational pathways.MethodsThis exploratory case study develops and evaluates an eight-week blended course, DeSci EDU, which combines theory-based seminars, scaffolded assignments, and alumni mentorship. Thirty-two participants completed pre-course self-assessments across ten blockchain and DeSci domains; 22 provided post-course data, and 11 supplied matched identifiers.ResultsCohort means increased by 41% for blockchain and 53% for DeSci, with the largest relative gains in governance mechanisms and token-based incentives. Matched-pair analysis showed comparable improvements (+51% and +58%).DiscussionThe early-career, highly educated sample and reliance on self-report limit generalizability and causal attribution. Nonetheless, the results suggest that a structured practice-oriented curriculum can quickly enhance DeSci literacy. Future iterations should integrate objective performance tasks, transversal competencies, and automated participant tracking to enable scalable and rigorous evaluation.